Perencanaan Ruangan dan Pagar Kantor Desa di Desa Lamomea Kecamatan Konda Kabupaten Konawe Selatan - Hado Hasina; Sitti Hawa; La Ode Muh. Zulfitrah W; Muh. Ibrahim Amin; Bintang Pandawa Five (CV. Multi Kreasi Media, 2023)
The Village Office is the service center in the Village, being the center of all activities in the Village, whether in the areas of Government, Empowerment, Development or Coaching, all centered at the Village Office. The existence and condition of a village office can reflect the identity of the village itself, it is not uncommon for people to look at the office alone to determine the value of a village as a whole. Because of this, it would not be wrong for the village administration to program the construction of a proper office. A proper office is an office that is good for service and provides a sense of comfort for every resident who wants to report or simply requests mailing services and is able to make village employees feel at home at work. This service activity was carried out for two weeks from January 18-31 2023 at Lamomea village, Konda sub disctrict, South Konawe regency and involving Civil Engineering students at the University of Southeast Sulawesi and community participation.